Effect of Glycerol and Stearic Acid as Plasticizer on Physical Properties of Benzylated Wheat Straw - Jamshid Mohammadi Rovshandeh; Kamel Ekhlasi Kazaj; Ashkan Hosseini; Peyman Pouresmaeel Selakjani (Iranian Journal of Chemistry & Chemical Engineering, 2014)
The wheat straw as abundant lignocellulosic resource was successfully undergone in a benzylation reaction and plasticized with different contents (2.5, 3, 5 and 7 wt. %) of glycerol and stearic acid.The effect of type and concentration of plasticizers on the mechanical, thermomechanical, morphological and water absorption properties of Benzylated Wheat Straw (BWS) was investigated by tensile, Dynamic Mechanical Thermal Analysis (DMTA) measurements and Scanning Electron Microscopy (SEM), respectively. The experimental results show that addition of plasticizer may increase the elongation at break and may decrease the tensile strength for the sheet plasticized with 5% or 7% stearic acid and 3% or 5% glycerol. The addition of 7% glycerol or 3% stearic acid makes increase both tensile strength and elongation at break. These films are stronger but less tough compared to unplasticized BWS film. The porosity at the surfaces of samples from the SEM micrographs showed good correlation with the mechanical properties of the blends.On addition of plasticizer, it is observed that there is a decrease in the size of micropores and for higher concentration, it no longer exists. Compared with glycerol, the water absorption of the BWS films plasticized with stearic acid was significantly lower. Glycerol is soluble in water and removed from films after floating in water. The film plasticized with 2.5% both glycerol and stearic acid had better water resistance than others. As usual, glass transition temperatures of samples were decreased by addition of plasticizers according to DMTA results.